Nilai Pendidikan dalam Novel Rantau 1 Muara karya A. Fuaddi - Zira Fatmaira (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aims to describe the description of the value of education in the novel Rantau 1 Muara by A Fuaddi. The data of this study is a description of the value of education in terms of the value of divine education, the value of moral education, the value of social education, the value of cultural education and the value of aesthetic education. The method used is descriptive method with qualitative analysis by describing the description of the value of education in the novel Rantau 1 Muara by A Fuaddi with an educational value approach. This method is based on consideration of the suitability of the research form with the research objectives. The research instrument was carried out by means of a documentation study. Documentation study was conducted on the novel Rantau 1 Muara by A Fuaddi with an educational value approach. From the results of this study, information on the value of education in terms of the value of divine education can be obtained. I stuck the used ticket with tambourine nails on the map. Alhamdulillah, man jadda wajada is again effective. the value of moral education, not pleasant to hear. maybe this time he was disturbed by the sound of a hammer hitting the wall. Punten, Mom, I said hastily opened the bedroom door and apologized. But his attention was apparently not on the sound of the hammer. the value of social education, life is essentially an immigrant. A time will return to the roots, to the one, to the beginning, yaita, the Almighty. the value of cultural education In Washington, Alif and Dinara live together. But in the family there are symptoms, namely they still can't manage money to save money. It's not wasteful but Dinara wants to buy household appliances, but Alif teaches Dinara to save money and the value of aesthetic education. "My feelings have met, but where?" Alif said in his heart. Until Alif had to chase after him, when he left his initial interview as a journalist. Alif was teased by the editorial staff, "I have a crush, he is a new child here, just pray that he will be accepted?"